BRYANSK-KURSK-VORONEZH INTRA-CONTINENTAL COLLISIONAL OROGEN (EAST EUROPEAN CRATON) - M. V. Mints; W. A. Bush; S. N. Ageev (Геодинамика и тектонофизика)
The article presents new data on the deep crustal structure, origin and evolution of the Bryansk-Kursk-Voronezh orogen in the south-eastern segment of the East European craton; it is composed of the Paleoproterozoic formations and areas of reworked Archean crust. The purpose of this paper is the development and improvement of ideas on intra-continental orogens. The deep structure of the orogen is presented by the 3D model based on results of geological mapping of the Precambrian basement and interpretations of geophysical fields and seismic images of the crust along geotraverse 1-EB and profile DOBRE. It is established that the orogen originated with riftogenic extension of the crust at 2.6–2.5 Ga, that was repeated at 2.2–2.1 Ga, and formation of wide depressions that were efficiently filled in with volcanosedimentary layers including BIF, which accumulation was followed by high-temperature up to granulite facies metamorphism. Suprasubduction magmatism took place at 2.10–2.08 Ga and resulted in formation of the Lipetsk-Losevka volcano-plutonic complex. The active margin was completely formed at about 2.05 Ga. The short duration of subduction-related magmatic activity and the lack of relics of the oceanic lithosphere suggest short-term and spatially limited developing of the oceanic structure. The tectonothermal activity of collisional and postcollision stages was expressed in emplacement of alkaline ultramafic (2.1–2.0 Ga) and gabbro-syenite (1.8–1.7 Ga) complexes. It is difficult or impossible to explain specific features of the structure and evolution of the orogen in framework of the model of the Cordilleras type  accretionary orogen. Mafic-ultramafic magmatism and indications of intensive heating of the crust suggest a special role of plume type processes that provided for influx of mantle heat and juvenile mantle derived matter.